2018
DOI: 10.1016/j.ajem.2017.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with imaging overuse in the emergency department: A systematic review

Abstract: The literature is heterogeneous with surprisingly few studies of determinants of imaging in minor head injury or of spine imaging. Older patient age and higher ISS were the most consistently associated with ED imaging overuse. This review highlights the need for precise definitions of overuse of imaging in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 40 publications
2
38
2
3
Order By: Relevance
“…Both health systems offer universal healthcare. In the USA, a recent systematic review of determinants of imaging in the ED found that imaging overuse was greater in older patients . Comparing geriatric services and testing practices across different systems of care would be valuable in the identification of practices that can reduce variation between hospital ED.…”
Section: Discussionmentioning
confidence: 99%
“…Both health systems offer universal healthcare. In the USA, a recent systematic review of determinants of imaging in the ED found that imaging overuse was greater in older patients . Comparing geriatric services and testing practices across different systems of care would be valuable in the identification of practices that can reduce variation between hospital ED.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing these strategies and their effectiveness at reducing imaging is a popular topic in the literature with several systematic reviews having been published. However, this literature frequently focuses on specific pathologies (e.g., CT use in acute low-back pain patients), includes multiple imaging modalities, or reviews the incidence of low-value testing in general without addressing potential solutions [7,[10][11][12][13][14][15].…”
Section: Description Of the Existing Intervention Datamentioning
confidence: 99%
“…A recent review has identified three factors that predisposes the overuse of radiological imaging in emergency departments-poor integration of services, overcrowding or reduced staffing levels, and a litigious environment that encourages the practice of defensive medicine (15).…”
Section: Ct Use Has Increased Rapidlymentioning
confidence: 99%